CIDP presenting as recurrent severe back pain without weakness or sensory loss. Issue 6 (16th June 2016) - Bäumer, Dirk; Grant, David James; Knight, Ravi; Buckley, Camilla; Bennett, David; Rinaldi, Simon
Abstract : A 71-year-old woman presented with severe back pain, limb weakness and cranial nerve dysfunction associated with high cerebrospinal fluid (CSF) protein; we diagnosed Guillain-Barré syndrome and her symptoms completely resolved after intravenous immunoglobulin. Over the next 4 years, she had three further episodes of excruciating back pain accompanied by raised CSF protein, but without weakness, sensory loss, or abnormalities in routine nerve conduction studies. Sensory evoked potentials suggested proximal demyelination and lumbosacral plexus imaging suggested inflammation. We argue that this is a relapsing proximal polyradiculoneuropathy on the spectrum of chronic inflammatory demyelinating polyradiculoneuropathy.